Comparison on Response and Dissolution Rates Between Ursodeoxycholic Acid Alone or in Combination With Chenodeoxycholic Acid for Gallstone Dissolution According to Stone Density on CT Scan: Strobe Compliant Observation Study. Issue 50 (December 2015) - Lee, Jae Min; Hyun, Jong Jin; Choi, In Young; Yeom, Suk Keu; Kim, Seung Young; Jung, Sung Woo; Jung, Young Kul; Koo, Ja Seol; Yim, Hyung Joon; Lee, Hong Sik; Lee, Sang Woo; Kim, Chang Duck
Abstract : Abstract: Medical dissolution of gallstone is usually performed on radiolucent gallstones in a functioning gallbladder. However, absence of visible gallstone on plain abdominal x-ray does not always preclude calcification. This study aims to compare the response and dissolution rates between ursodeoxycholic acid (UDCA) alone or in combination with chenodeoxycholic acid (CDCA) according to stone density on computed tomography (CT) scan. A total of 126 patients underwent dissolution therapy with either UDCA alone or combination of CDCA and UDCA (CNU) from December 2010 to March 2014 at Korea University Ansan Hospital. In the end, 81 patients (CNU group = 44, UDCA group = 37) completed dissolution therapy for 6 months. Dissolution rate (percentage reduction in the gallstone volume) and response to therapy (complete dissolution or partial dissolution defined as reduction in stone volume of >50%) were compared between the 2 groups. Dissolution and response rates of sludge was also compared between the 2 groups. The overall response rate was 50.6% (CNU group 43.2% vs UDCA group 59.5%, P = 0.14), and the overall dissolution rate was 48.34% (CNU group 41.5% vs UDCA group 56.5%, P = 0.13). When analyzed according to stone density, response rate was 33.3%, 87.1%, 30.0%, and 6.2% for hypodense, isodense, hyperdense, and calcified stones, respectively. Response rate (85.7% vs 88.2%, P = 0.83) and dissolution rate (81.01% vs 85.38%, P = 0.17) of isodense stones were similar between CNU and UDCA group. When only sludge was considered, the overall response rate was 87.5% (CNU group 71.4% vs UDCA group 94.1%, P = 0.19), and the overall dissolution rate was 85.42% (CNU group 67.9% vs UDCA group 92.7%, P = 0.23). Patients with isodense gallstones and sludge showed much better response to dissolution therapy with CNU and UDCA showing comparable efficacy. Therefore, CT scan should be performed before medication therapy if stone dissolution is intended.